Draft Annual Plan (2003-2004) Government of Himachal Pradesh - Planning Commission (Planning Commission, 2003)
As per latest State Forest Report, an area of 12,501 Sq. Km. is actual forest area with density ranging from 10% to 40% and above. This is constituted by 9,565 Sq. Km. of dense forests, having a crown density of 40% and above and 2,936 Sq. Km. with crown density between 10 to 40%. In addition to this 1845 Sq. Km. has been described as scrubs.
Planning Department, Government of Himachal Pradesh